(untitled) (Research, Society and Development, 2022)
Objective: To analyze the main challenges and difficulties in Nursing care provided to people living with HIV/AIDS. Methodology: This is an integrative literature review. The integrative review includes the analysis of relevant research that supports decision making and the improvement of clinical practice. This research method allows the synthesis of multiple published studies and allows general conclusions regarding a particular area of ​​study. Results and Discussion: Prejudice and stigma represent difficulties in providing care, since professionals bring perceptions regarding the historical context of the disease in the form of blaming the person, which directly interferes with the quality of care provided, due to weakening ties between both parties. Conclusion: It is observed that prejudice is the challenge to be overcome to improve nursing care, in all analyzed articles prejudice stands out in all, with this it is contacted that in order to provide good care, the need for a good interpersonal relationship between patient and nurse.